Pengaruh Kompensasi Finansial Dan Motivasi Intrinsik Terhadap Kepuasan Kerja Auditor (Studi Kasus Kantor Inspektorat Daerah Kota Binjai) - Muhammad Farhan Alyusri; M. Ridwan; Khairina Tambunan (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study uses quantitative methods involving 51 respondents.  Data was collected by using the distribution of questionnaires.  The data obtained were analyzed using statistical formulas, namely by using multiple regression analysis carried out with the SPSS 25 program. The results of the multiple linear regression analysis were that the independent variable was considered zero, so the value of job satisfaction was 1.219.  If there is an increase in financial compensation by 1, then job satisfaction (Y) will increase by 0.474.  If there is an increase in intrinsic motivation of 1, then job satisfaction (Y) will increase by 0.273. The financial compensation variable has the greatest influence on job satisfaction 0.474, then followed by the intrinsic motivation variable of 0.273.  The results of this analysis using the determinant coefficient is known that 40,% variation of job satisfaction can be explained by financial compensation and intrinsic motivation at a confidence level of 0,05%.  While the remaining 60% is explained by other variables not included in this study. The results of quantitative analysis show that the variables of financial compensation and intrinsic motivation have a significant simultaneous effect on auditor job satisfaction.  This study describes the need for financial compensation and intrinsic motivation on auditor job satisfaction at the Binjai City Regional Inspectorate Office.